Specification for alternating current disconnectors and earthing switches (BSI, 1990)
Switches, Earthing switches, Electrical protection equipment, Alternating current, Isolator switches, Voltage, Performance, Electrical insulation, Rated voltage, Withstand voltage, Ratings, Rated current, Loading, Marking, Testing conditions, Endurance testing, Mechanical testing, Environmental testing, Test equipment, Electrical testing, Selection